LISTENING ANXIETY OF ENGLISH AS A FOREIGN LANGUAGE - Muhammad Alim Akbar Nasir; Wilma Prafitri (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
This research aimed to (1) discover the profile of the students’ listening anxiety; (2) reveal the students’ English listening comprehension; and (3) uncover whether there is a correlation between students’ listening anxiety and their English Listening Comprehension. This research was designed quantitatively by employing correlational analysis. The sample chosen was 35 fourth semester students in English Department of Universitas Islam Makassar. The instruments were listening anxiety questionnaire consisted of 33 items adopted from Chang (2008) and listening and listening comprehension test consisted of 50 items by Phillips (2001). The results of the instruments were analyzed quantitatively which were then analyzed by using SPSS 21 for the correlational analysis. The results showed that the mean score of the listening anxiety questionnaire was 120.77 which can be concluded as medium anxiety level. Meanwhile, the mean score of the students’ English listening test was 43.14 which could be concluded as fair listening comprehension. Furthermore, the correlational analysis showed that the value of the r-computed was -0.748 meaning that H0 was rejected and Ha was accepted and since the result of the r-computed was negative, it can be concluded that there was strong negative correlation between listening anxiety and listening comprehension of the students meaning that the higher the listening anxiety of the students is, the lower the students’ listening comprehension is and vice versa.